2015
DOI: 10.1063/1.4905231
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of edge localised modes and edge localised mode control

Abstract: Edge Localised Modes (ELMs) in ITER Q ¼ 10 H-mode plasmas are likely to lead to large transient heat loads to the divertor. To avoid an ELM induced reduction of the divertor lifetime, the large ELM energy losses need to be controlled. In ITER, ELM control is foreseen using magnetic field perturbations created by in-vessel coils and the injection of small D2 pellets. ITER plasmas are characterised by low collisionality at a high density (high fraction of the Greenwald density limit). These parameters cannot sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 120 publications
(194 reference statements)
2
48
0
Order By: Relevance
“…The increase in plasma stored energy is limited by the onset of periodic bursts called Edge Localised Modes (ELMs) [3][4][5][6][7][8][9], each of which leading to a transient collapse of the pedestal. Understanding these modes is imperative for correctly predicting fusion performance and controlling ELMs in ITER [10,11]. The most widely accepted model to explain the occurrence of ELMs is the peeling ballooning (PB) model [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The increase in plasma stored energy is limited by the onset of periodic bursts called Edge Localised Modes (ELMs) [3][4][5][6][7][8][9], each of which leading to a transient collapse of the pedestal. Understanding these modes is imperative for correctly predicting fusion performance and controlling ELMs in ITER [10,11]. The most widely accepted model to explain the occurrence of ELMs is the peeling ballooning (PB) model [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of non‐linear simulations of ELMs and their control by various codes can be found in ref. [].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, non-linear MHD modelling, using JOREK [27], M3D-C1 [28,29], BOUT++ [30], NIMROD [31], as has been well summarised in Ref. [32] , has provide crucial understanding of the ELM and ELM control physics.…”
Section: Introductionmentioning
confidence: 99%